Duty of care between actors in supply chains - Goudkamp, J (Sweet and Maxwell, 2017)
Considers the potential duty of care which a company within a supply chain may owe to employees of another organisation within the chain, despite the principle that such a duty does not arise to control third parties. Examines whether the rulings in Chandler v Cape Plc (CA) and Thompson v Renwick Group Plc (CA) have changed the situation, and assesses the prospects of success using either the Caparo test or the assumption of responsibility test.